Approaching the Limits of Aspect Ratio in Free‐Standing Al2O3 3D Shell Structures. Issue 10 (17th May 2022) - Burgmann, Stephanie; Lid, Markus; Chaikasetsin, Settasit; Bjordal, Dag Skjerven; Prinz, Fritz; Provine, John; Berto, Filippo; van Helvoort, Antonius T. J.; Torgersen, Jan
Abstract : Nanoscale free‐standing membranes are used for a variety of sensors and other micro/nano‐electro‐mechanical systems devices. To tune performance, it is indispensable to understand the limits of aspect ratios achievable. Herein, vapor hydrofluoric (VHF) processes are employed to release 3D shell structures made of atomic‐layer‐deposited Al2 O3 etch‐stop layers. Structure heights of 100–600 nm and widths of 1–200 nm are fabricated for membranes with 20 and 50 nm thickness. Undercut depths of 500 μ m and aspect ratios of 475:1 etch depth to structure width (50 nm films) and etch depth to membrane thicknesses of 495:0.02 (20 nm films) are achieved. The etch‐rate stagnates above a ratio of 31% hydrofluoric (HF), where decreasing EtOH shares reduce reproducibility. Etch rates reach 0.75 mm min −1 and are generally constant over vapor etch depth. For 100 nm heights and widths of 2 μ m, etch rates however stagnate for deeper depths. All explored structures remained stable with widths up to 5 μm independent of the height. Above 10 μ m width, top membranes deflect, likely from stress accumulated during deposition. Herein, exploring and understanding the limits of aspect ratio in future free‐standing membrane devices are helped. Abstract : Tunnel like nano structures with down to 20 nm shell thickness and up to 500 μm length are fabricated via atomic layer deposition of alumina and hydrogen fluoride vapor release etching rendering aspect ratios of up to 475:1 etch depth to structure width and 295:0.02 etch depth to shell thickness. Straightforward geometric design allows tuning their mechanical response.